2018
DOI: 10.1016/j.carbpol.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

The interfacial, emulsification and encapsulation properties of hydrophobically modified inulin

Abstract: Octenyl- and dodecenyl succinic anhydride derivatives (OSA- and DDSA-) of inulin have been synthesised and their solution and interfacial properties have been determined and compared to a commercially available alkylated inulin, Inutec SP1. All samples formed micellar aggregates in solution above a critical concentration (critical aggregation concentration) and were able to 'dissolve' a hydrophobic dye. They were also able to form stable oil-in-water (O/W) emulsions as assessed by measurements of their droplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
(33 reference statements)
0
26
0
Order By: Relevance
“…The zeta potential of the OSA inulin derivative was observed to increase (-4.8 mV to -60.8 mV) with increasing pH (1.9 to 9.7), whereas that of the DDSA-inulin derivative was found to increase (2.2 mV–55.5 mV) within a pH range of 1.8–10.2. The results of droplet size as a function of time and temperature were assessed for the DDSA-inulin derivative, OSA inulin derivative, and Inutec®SP1, and it was observed that the DDSA-inulin derivative showed the greatest emulsification properties (smaller droplet size) of the three compounds ( Kokubun et al, 2018 ). The same research group studied the emulsification properties of OSA inulin derivatives and DDSA-inulin derivatives in the presence of electrolytes and during storage.…”
Section: Chemistry and Synthesis Of Hmimentioning
confidence: 99%
See 2 more Smart Citations
“…The zeta potential of the OSA inulin derivative was observed to increase (-4.8 mV to -60.8 mV) with increasing pH (1.9 to 9.7), whereas that of the DDSA-inulin derivative was found to increase (2.2 mV–55.5 mV) within a pH range of 1.8–10.2. The results of droplet size as a function of time and temperature were assessed for the DDSA-inulin derivative, OSA inulin derivative, and Inutec®SP1, and it was observed that the DDSA-inulin derivative showed the greatest emulsification properties (smaller droplet size) of the three compounds ( Kokubun et al, 2018 ). The same research group studied the emulsification properties of OSA inulin derivatives and DDSA-inulin derivatives in the presence of electrolytes and during storage.…”
Section: Chemistry and Synthesis Of Hmimentioning
confidence: 99%
“…Inulin, which was discovered as a fructan-type oligosaccharide, is distributed in more than 36,000 vegetables and herbs. Jerusalem artichokes, leeks, oats, onion, and garlic are abundant sources of inulin, while it is obtained commercially from members of the Asteraceae family, such as chicory ( Afinjuomo et al, 2019 ; Kokubun, Ratcliffe, & Williams, 2018 ). Inulin is made up of d -fructose units that are linked by β-2,1 glycosidic bonds with a wide range of degrees of polymerization (between 2 and 60) and commonly combined with a glucose residue at the terminus ( López-Molina et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that availability of b-carotene enhanced along with the increasing DS of OSA modied starches, which was consistent with previous studies. 18,30,45 For example, 5% OSA@PS sample have the excellent bioaccessibility, due to the DS up to 0.0289. Compared with OSA@NS samples, the bioaccessibility of OSA@PS emulsions showed almost twice than that of OSA@NS.…”
Section: Determination Of Bioaccessibility Of B-carotenementioning
confidence: 99%
“…Additionally, inulin can be considered a renewable material in bioprocesses for biofuel production. The biocompatible, biodegradable, renewable, and hydrophilic structure, along with natural and plant‐based origin, make inulin a very attractive material for diverse applications 12‐14 …”
Section: Introductionmentioning
confidence: 99%